The development of social intelligence in the future leaders of educational institutions - Редько, Сергій (Educological discourse, 2013)
The article is devoted to the analysis of psychological determinants of development of the social intellect for the students-future leaders of establishments of education. Influence of the socially-psychological factors on a social intellect is examined here.